Flowmeter performance comparison downstream of double 90° elbows out‐of‐plane. Issue 1 (10th January 2019) - Day, Matthew P.; Johnson, Michael C.; Barfuss, Steven L.
Abstract : This study was completed to investigate the performance of six flowmeters placed at five diameters and, in some cases, zero diameters downstream from a double elbow out‐of‐plane (DEOP) in a laboratory piping installation. Each meter was installed in a straight pipeline and calibrated against a weight tank providing a baseline level of performance for each meter. A DEOP was set up, with the flowmeters installed at the desired downstream positions where each meter's performance was assessed. The baseline and the DEOP calibration results were compared with one another. The plausibility of using various types of flowmeters under similar conditions when cost and space do not allow for adequate upstream and downstream lengths of pipe is demonstrated in the results. In circumstances where the accuracy requirements of the installation go beyond those of this study, a physical laboratory calibration in a simulated pipe will be necessary.